The role of antimicrobial peptides in chronic inflammatory skin diseases - Marcinkiewicz, Małgorzata; Majewski, Sławomir (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Antimicrobial peptides (AMPs) are effector molecules of the innate immune system of the skin. They present an activity against a broad spectrum of Gram-positive and Gram-negative bacteria as well as some fungi, parasites and enveloped viruses. Several inflammatory skin diseases including psoriasis, atopic dermatitis, acne vulgaris and rosacea are characterized by a dysregulated expression of AMPs. Antimicrobial peptides are excessively produced in lesional psoriatic scales or rosacea in contrast to the atopic skin that shows lower AMP levels when compared with psoriasis. The importance of the AMPs contribution to host immunity is indisputable as alterations in the antimicrobial peptide expression have been associated with various pathologic processes. This review discusses the biology and clinical relevance of antimicrobial peptides expressed in the skin and their role in the pathogenesis of inflammatory skin diseases.